2023
DOI: 10.18240/ijo.2023.05.13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and multimodal imaging features of acute macular neuroretinopathy lesions following recent SARS-CoV-2 infection

Abstract: AIM: To describe the clinical characteristics of eyes using multimodal imaging features with acute macular neuroretinopathy (AMN) lesions following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. METHODS: Retrospective case series study. From December 18, 2022 to February 14, 2023, previously healthy cases within 1-week infection with SARS-CoV-2 and examined at Tianjin Eye Hospital to confirm the diagnosis of AMN were included in the study. Totally 5 males and 9 females [mean age: 29.93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In fact, viral particles following infection with SARS-CoV-2 possibly cause choroidal vasculopathy (42). Bellur et al and Liu et al reported that the choriocapillaris vascular density was reduced in AMN after SARS-CoV-2 infection using OCT angiography (22,38). In our case, SARS-CoV-2 virion attached presumed ACE2-positive choroidal vessels, led to acute choroidal bloodstream congestion, and impaired choroidal circulation, which subsequently reduced stromal and in vivo luminal areas at the acute phase of infection.…”
Section: Initial Findings On Laser Speckle Flowgraphy (Lsfg) and Opti...mentioning
confidence: 99%
“…In fact, viral particles following infection with SARS-CoV-2 possibly cause choroidal vasculopathy (42). Bellur et al and Liu et al reported that the choriocapillaris vascular density was reduced in AMN after SARS-CoV-2 infection using OCT angiography (22,38). In our case, SARS-CoV-2 virion attached presumed ACE2-positive choroidal vessels, led to acute choroidal bloodstream congestion, and impaired choroidal circulation, which subsequently reduced stromal and in vivo luminal areas at the acute phase of infection.…”
Section: Initial Findings On Laser Speckle Flowgraphy (Lsfg) and Opti...mentioning
confidence: 99%